Educational Inst itutions’ Disclosure of Financial Report in the Form of Sustainability Report - Peatrat, Nopporn; Rochanasak, Sirikorn; Suwannasri, Niroumon; konginta, Wanrapa (Journal of Multidisciplinary in Social Sciences, 2022)
Disclosure of information accompanying financial report, especially information that represents the educational institutions’ sustainability for stakeholders and users of financial reports to have confidence in the educational institution’s learning management and its quality. Therefore, it is imperative that education administrators understand, respond to and meet the expectations and needs of stakeholders by disclosing financial reports information in accordance \with sustainability reporting guidelines. Furthermore, the report can be served as an assessment tool when evaluating the institution’s performance. Other than financial report, stakeholders and related parties can also access to other needed information. The report’s important areas comprise of Environmental Dimension which applies to the impact of the organization have on living and non-living things, including ecosystems, soil, air and water; Social Dimension refers to the impact on social system caused by the organization's operation, and Governance and Economic Dimensions are the impact of the organization has on the overall economic system of stakeholders at the local, national and global levels.